2020
DOI: 10.1099/ijsem.0.004158
|View full text |Cite
|
Sign up to set email alerts
|

Nocardiopsis deserti sp. nov., isolated from a high altitude Atacama Desert soil

Abstract: The taxonomic status of a Nocardiopsis strain, designated H13T, isolated from a high altitude Atacama Desert soil, was established by using a polyphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
(72 reference statements)
4
10
0
Order By: Relevance
“…dassonvillei DSM 43111 T as determined through dDDH was near the dDDH threshold (79-80 %) proposed for delineating subspecies within bacterial and archaeal species [49]. Together, phenotypic and genomic differences justify the classification of strain D1 T as a new ) the species delineation threshold, the whole genome sequence based divergence values detected in the present study (Table 1) and by Nouioui et al [33] and Asem et al [34] were clearly below those of the whole genomic sequence based thresholds [29,30] and demonstrate that the classification of this taxon as a distinct Nocardiopsis species is more appropriate. The latter classification is also in line with differences in menaquinone and cell wall teichoic acid content, and in several growth and physiological characteristics [6,34].…”
Section: Physiology and Chemotaxonomysupporting
confidence: 75%
See 4 more Smart Citations
“…dassonvillei DSM 43111 T as determined through dDDH was near the dDDH threshold (79-80 %) proposed for delineating subspecies within bacterial and archaeal species [49]. Together, phenotypic and genomic differences justify the classification of strain D1 T as a new ) the species delineation threshold, the whole genome sequence based divergence values detected in the present study (Table 1) and by Nouioui et al [33] and Asem et al [34] were clearly below those of the whole genomic sequence based thresholds [29,30] and demonstrate that the classification of this taxon as a distinct Nocardiopsis species is more appropriate. The latter classification is also in line with differences in menaquinone and cell wall teichoic acid content, and in several growth and physiological characteristics [6,34].…”
Section: Physiology and Chemotaxonomysupporting
confidence: 75%
“…It also showed that N. dassonvillei subsp. albirubida DSM 40465 T formed a distinct lineage as previously demonstrated by Asem et al [34].…”
Section: Whole Genome Sequence Analysissupporting
confidence: 75%
See 3 more Smart Citations